NEW TAXA OF BENTHIC FORAMINIFERS FROM THE PALEOGENE OF THE COMMONWEALTH OF INDEPENDENT STATES - Bugrova E.M. (My University, 2001)
New taxa of benthic foraminifers from the order Nodosariida are described: Turkmenicaellinae subfam. nov.; Dolosia gen nov.; D. alpha sp. nov.; Hydromylinella gen. nov.; H. wittpyuti sp. nov., H. plana sp. nov.; and Fursenkoella gen. nov. The new genus Pilleusella J. Nikitina in Bugrova (order Rotaliida) is established. Two new species assigned to the genera previously unknown from the Lower Eocene of the Commonwealth of Independent States are described, i.e., Caucasina inflata sp. nov. (order Rotaliida) and Cuvillierina cristata sp. nov. (order Buliminida).
Keywords: Foraminifers; Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген